Age and sex-specific differences in interleukin 4, interferon gamma, macrophage migration inhibitory factor, and vascular endothelial growth factor levels in the tears of healthy subjects - Mravec Bencúrová, Dominika; Mandíková, Šárka; Daňková, Pavlína (European journal of ophthalmology, 2022)
OBJECTIVE: To investigate the physiological profile of pro-inflammatory and anti-inflammatory cytokines in tears produced by epithelial cells under the effect of endogenous and exogenous biological factors. Knowing the physiological cytokine profile in tears with its biological characteristics including sex- and age-specific effects is fundamental when tears are analyzed for diagnostic or prognostic purposes in eye diseases. METHODS: Tear samples were collected from right eye of 45 healthy volunteers (24 males, 21 females) by 5 μl microcapillary tube. Cytokines interleukin 1β, interleukin 10, interleukin 4, interferon gamma, macrophage migration inhibitory factor, and vascular endothelial growth factor were quantified by multiplex Bio-Plex system. RESULTS: The production of macrophage migration inhibitory factor cytokine by epithelial cells on the ocular surface is higher in males compared to females (p = 0.05); actually, most of female tear samples present with undetectable macrophage migration inhibitory factor levels. Our results show the negative correlations between the age and concentrations of interleukin 4 (p < 0.01) and interferon gamma (p < 0.01) in tears, respectively, and positive associations of vascular endothelial growth factor levels with the age above 45 years (p < 0.05). CONCLUSIONS: Data in this study indicate that age and sex may affect the physiological levels of cytokines in tears. Consequently, the impacts of biological factors need to be recognized and taken into consideration before the levels of cytokines in patients' tears are analyzed for medical reasons. Concentrations of interleukin 1β and interleukin 10 cytokines, however, are very low in healthy tears and do not seem to be influenced by studied biological factors; therefore, they meet the requirements for analytes suitable for medical diagnostic and prognostic purposes.
Keywords: Humans; Macrophage Migration-Inhibitory Factors; Vascular Endothelial Growth Factor A; Tears; Interleukin-4; zdraví dobrovolníci pro lékařské studie; mužské pohlaví; Age Factors; vaskulární endoteliální růstový faktor A; interleukin-4; inhibiční faktory migrace makrofágů; Sex Factors; slzy; Interleukin-10; Interferon-gamma; ženské pohlaví; sexuální faktory; věkové faktory; lidé; interferon gama; interleukin-10; interleukin-1beta; Male; Interleukin-1beta; Healthy Volunteers; Female